2000
DOI: 10.1074/jbc.m003250200
|View full text |Cite
|
Sign up to set email alerts
|

Sequence-specific DNA Recognition by the Myb-like Domain of Plant Telomeric Protein RTBP1

Abstract: We have identified a rice gene encoding a DNA-binding protein that specifically recognizes the telomeric repeat sequence TTTAGGG found in plants. This gene, which we refer to as RTBP1 (rice telomere-binding protein 1), encodes a polypeptide with a predicted molecular mass of 70 kDa. RTBP1 is ubiquitously expressed in various organs and binds DNA with two or more duplex TTTAGGG repeats. The predicted protein sequence includes a single domain at the C terminus with extensive homology to Myb-like DNA binding moti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
86
1
1

Year Published

2003
2003
2016
2016

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 98 publications
(91 citation statements)
references
References 45 publications
(36 reference statements)
3
86
1
1
Order By: Relevance
“…6B). These results are in line with the previous observations that rice RTBP1 and Arabidopsis AtTBP1 are ubiquitously present in various parts of plants (40,42). To investigate whether NgTRF1 expression is correlated with tissue development, roots were serially dissected according to different developmental stages (sections 1-4), and total RNAs from each section were subjected to RNA gel blot analysis.…”
Section: Resultssupporting
confidence: 71%
See 1 more Smart Citation
“…6B). These results are in line with the previous observations that rice RTBP1 and Arabidopsis AtTBP1 are ubiquitously present in various parts of plants (40,42). To investigate whether NgTRF1 expression is correlated with tissue development, roots were serially dissected according to different developmental stages (sections 1-4), and total RNAs from each section were subjected to RNA gel blot analysis.…”
Section: Resultssupporting
confidence: 71%
“…Gel retardation assays showed that the Myb domain of both the rice and Arabidopsis proteins was able to bind to double-stranded, but not single-stranded, plant telomeric DNA (40 -42). The mRNAs for rice RTBP1 and Arabidopsis AtTBP1 were ubiquitously present in all tissues examined (40,42). However, these studies did not provide any information about the physiological roles and developmental regulation patterns of these telomere-related genes.…”
mentioning
confidence: 75%
“…The complex structure of subtelomere regions with various units of tandem or interspersed repeats has been shown to represent chromosome identity in several mammalian and lower eukaryotic organisms (Higashiyama et al 1997;Myler et al 1999;Kojima et al 2002;Sunkin et al 2002). In plant genomes, very little information on subtelomere sequence is available (Richards et al 1992) compared with the abundance of data obtained from numerous functional studies with telomeres and related proteins (Riha et al 2000(Riha et al , 2001Yu et al 2000;Chen et al 2001;Gallego and White 2001;Bundock and Hooykaas 2002;Riha and Shippen 2003). The two TATRs found on chromosomes 7 and 10 showed totally different and unique repeat sequences.…”
Section: Sequence Characteristics Of Tatr7 and Tatr10smentioning
confidence: 99%
“…28) Rice RTBP1 is categorized as type I and also binds telomeric DNA. 29) These characteristics indicate that the type I proteins are telomeric DNAbinding proteins. Conversely, type II proteins of A. thaliana cannot bind telomeric DNA.…”
Section: Comparison Of the Amino Acid Sequence Of Ctmyb1 With Other Cmentioning
confidence: 99%
“…1(B)). 27) A phylogenetic analysis of the sequences of the C-terminal Myb domain proteins of Arabidopsis thaliana, 28) rice (AK071645 and AK242392), 29,30) and Catharanthus roseus 25) revealed that this protein family is classified into 2 major groups: I and II (Supplemental Fig. 2).…”
Section: Comparison Of the Amino Acid Sequence Of Ctmyb1 With Other Cmentioning
confidence: 99%